PEMAHAMAN TERHADAP KATA PINJAMAN OLEH MAHASISWA PROGRAM STUDI BAHASA JEPANG UNIVERSITAS RIAU - Nurmalasari Nurmalasari; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: this research was aimed at finding out the understanding of Japanese loanwords of students of Japanese Department Universitas Riau. This research is descriptive qualitative, to obtain data, the instrument used in this research is written test. The number of the samples is 40 of the third-semester students of Japanese Department Universitas Riau . This study found that r-obtained is 46,1. In other words students understanding of the loanwords is still low.Keywords: Comprehension, Loanwords